(untitled) (Purbanchal University Health Journal, 2022)
Introduction: About 270 million workers meet occupational accidents estimated by the International Labor Organization (ILO). Metal workers are also exposed to accidents and injuries. However, there is little awareness on occupational health hazards in developing countries. Objective: The objective of the study was to assess the level of awareness of occupational health hazards and first aid management of metal workers of Patan Industrial Estate Lalitpur, Nepal. Method: Descriptive cross-sectional study was carried out among purposively selected 147 industrial metal workers who worked at least six months. By using structured interview schedule data was collected. Data were collected from 21 August 2018 to 16 September 2018. Descriptive and inferential statistics (Chi-square test) were used in data analysis. Result: The mean age of workers was 34.41 years (±11.85). Most of the workers were male (90.5%), literate (78.2%), iron workers (55.1%). The awareness level regarding occupational health hazards among workers was inadequate. Similarly, the level of awareness regarding first aid management was also inadequate among them. There was no association between the level of awareness on occupational health hazards and socio-demographic variables (age, sex, education and work experience) and further no association between level of awareness on first aid management and demographic variables (age, sex, education and work experience) was found. Conclusion: The level of awareness on occupational health hazards and first aid management in the present study was inadequate. Therefore, it is recommended to organize the educational program for improving awareness on occupational health hazards and first aid management.